Complete biodegradable nature of calcium hydroxylapatite after injection for malar enhancement: an MRI study - Pavicic T (Dove Medical Press, 2015)
Tatjana Pavicic Private Practice, Munich, Germany Background: Radiesse® (Calcium hydroxylapatite [CaHA]) is a biocompatible, injectable gel for facial soft tissue augmentation. It is a completely biodegradable filler and this is well documented, but objective imaging methods to confirm this property are scarce.Methods: We present a case report in which CaHA was injected into the midface of a 50-year-old woman for volume restoration and shaping of the cheek region. On the right side of the face, 1.6 mL CaHA was injected as several (5-7) small depots (0.1-0.2 mL) using a 28G 3/4 inch needle and the vertical supraperiosteal depot technique. On the contralateral side of the face, the subject received 1.6 mL CaHA over three entry points using a 27G 1 1/2 inch blunt cannula and the fanning technique. CaHA location and degradation were assessed using magnetic resonance imaging (MRI).Results: CaHA appears as low-to-intermediate signal intensity on MRI images taken immediately after injection for malar enhancement with a symmetrical distribution. On MRI images taken 2.5 years after injection, no CaHA was visible but tissue volume remained increased, indicating a collagen-stimulating effect. The treatment was well tolerated.Conclusion: In addition to producing long-lasting aesthetic and collagen-stimulating effects, MRI images confirm that CaHA is completely biodegradable with no product remaining 2.5 years after injection. Keywords: aesthetic, biodegradable, calcium hydroxylapatite, MRI, Radiesse